Nucleoporin NUP88/MOS7 is required for manifestation of phenotypes associated with the Arabidopsis CHITIN ELICITOR RECEPTOR KINASE1 mutant cerk1–4. (4th May 2017) - Genenncher, Bianca; Lipka, Volker; Petutschnig, Elena K.; Wiermer, Marcel
ABSTRACT: Arabidopsis nucleoporin MOS7/NUP88 was identified in a forward-genetic screen for components that contribute to auto-immunity of the deregulated Resistance ( R ) gene mutant snc1, and is required for immunity to biotrophic and hemi-biotrophic pathogens. In a recent study, we showed that MOS7 is also essential to mount a full defense response against the necrotrophic fungal pathogen Botrytis cinerea, suggesting that MOS7 modulates plant defense responses to different types of pathogenic microbes. Here, we extend our analyses of MOS7-dependent plant immune responses and report the genetic requirement of MOS7 for manifestation of phenotypes associated with the CHITIN ELICITOR RECEPTOR KINASE1 ( CERK1 ) mutant cerk1–4 .